Antecedents of green market performance: a case from Southeast Asian market. (2018) - Aqmala, Diana; Batu, Kardison Lumban; Kusumawardhani, Amie
This empirical research was conducted to investigate the effect of entrepreneurial orientation on the uniqueness of green products and market performance through green exploitative and explorative product capabilities, explorative and exploitative market penetration, and examining the effect of the uniqueness of green products on market performance. The exploitation and exploration of green product capabilities was considered as the antecedents and postulated as the driver of the uniqueness of green products, while exploitative and explorative market penetration were considered as the antecedents of market effectiveness. The current study proposes nine hypotheses. The statistical output showed that all hypotheses significantly affect green product differentiation and market performance but explorative market penetration is proven insignificant for leveraging market effectiveness. Data was collected from 1300 respondents charged as operational, sales, and marketing managers in Indonesia and several other Southeast Asian countries. Data was analysed using SEM with AMOS Statistical Software. This research demonstrated that green exploration and exploitation approaches to new product development practices hold a strategic anchor for enhancing green product differentiation and market performance.